GFR Slope as a Surrogate End Point for Kidney Disease Progression in Clinical Trials: A Meta-Analysis of Treatment Effects of Randomized Controlled Trials - Inker, Lesley A; Heerspink, Hiddo J L; Tighiouart, Hocine; Levey, Andrew S; Coresh, Josef; Gansevoort, Ron T; Simon, Andrew L; Ying, Jian; Beck, Gerald J; Wanner, Christoph; Floege, Jürgen; Li, Philip Kam-Tao; et al. (Journal of the American Society of Nephrology, 2019)
Surrogate end points are needed to assess whether treatments are effective in the early stages of CKD. GFR decline leads to kidney failure, but regulators have not approved using differences in the change in GFR from the beginning to the end of a randomized, controlled trial as an end point in CKD because it is not clear whether small changes in the GFR slope will translate to clinical benefits. To assess the use of GFR slope as a surrogate end point for CKD progression, we performed a meta-analysis of 47 RCTs that tested 12 interventions in 60,620 subjects. We estimated treatment effects on GFR slope (mean difference in GFR slope between the randomized groups), for the total slope starting at baseline, chronic slope starting at 3 months after randomization, and on the clinical end point (doubling of serum creatinine, GFR<15 ml/min per 1.73 m , or ESKD) for each study. We used Bayesian mixed-effects analyses to describe the association of treatment effects on GFR slope with the clinical end point and to test how well the GFR slope predicts a treatment's effect on the clinical end point. Across all studies, the treatment effect on 3-year total GFR slope (median =0.97; 95% Bayesian credible interval [BCI], 0.78 to 1.00) and on the chronic slope ( 0.96; 95% BCI, 0.63 to 1.00) accurately predicted treatment effects on the clinical end point. With a sufficient sample size, a treatment effect of 0.75 ml/min per 1.73 m /yr or greater on total slope over 3 years or chronic slope predicts a clinical benefit on CKD progress with at least 96% probability. With large enough sample sizes, GFR slope may be a viable surrogate for clinical end points in CKD RCTs.